2017
DOI: 10.1190/int-2016-0115.1
|View full text |Cite
|
Sign up to set email alerts
|

Controls on pore types and pore-size distribution in the Upper Triassic Yanchang Formation, Ordos Basin, China: Implications for pore-evolution models of lacustrine mudrocks

Abstract: Our main objectives are to (1) learn if pore-evolution models developed from marine mudrocks can be directly applied to lacustrine mudrocks, (2) investigate what controls the different pore types and sizes of Chang 7 organic matter (OM)-rich argillaceous mudstones of the Upper Triassic Yanchang Formation, and (3) describe the texture, fabric, mineralogy, and thermal maturity variation in the Chang 7 mudstones. Lacustrine mudstones from nine cored wells along a depositional dip in the southeastern Ordos Basin, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 48 publications
1
33
0
Order By: Relevance
“…Some of them appear to engulf pyrite grains (Fig.11A). As suggested in previous studies (Guo et al, 2018;Ko et al, 2017Ko et al, , 2018Loucks et al, 2012;Loucks and Reed, 2014;Milliken et al, 2013) these particles may correspond to migrated material resulting from kerogen conversion (bitumen, oil or preoil gel-like solid bitumen) probably mixed with amorphous kerogen particles. Locally, these OM particles exhibit a porous granular texture (Figs.10D, 11C).…”
Section: Om-hosted Pores and Surface Texturementioning
confidence: 56%
See 1 more Smart Citation
“…Some of them appear to engulf pyrite grains (Fig.11A). As suggested in previous studies (Guo et al, 2018;Ko et al, 2017Ko et al, , 2018Loucks et al, 2012;Loucks and Reed, 2014;Milliken et al, 2013) these particles may correspond to migrated material resulting from kerogen conversion (bitumen, oil or preoil gel-like solid bitumen) probably mixed with amorphous kerogen particles. Locally, these OM particles exhibit a porous granular texture (Figs.10D, 11C).…”
Section: Om-hosted Pores and Surface Texturementioning
confidence: 56%
“…For a given maturity, Ko et al (2018) showed that two mudstones characterized by differences in maceral composition can exhibit very different pore evolution models. Other non-maturity-related factors appear to have locally a significant effect on porosity such as the organic richness (Milliken et al, 2013;, the type or the original maceral composition of kerogen and its ability to produce oil (Cardott et al, 2015;Cardott and Curtis, 2018;Curtis et al, 2012;Guo et al, 2018;Ko et al, 2017Ko et al, , 2018Loucks et al, 2012;Mastalerz et al, 2013), the nature of the rock framework and the matrix porosity (Ko et al, 2017;Milliken et al, 2013;Pan et al, 2015). However, isolating the influence of these factors on porosity during burial and thermal maturation turns out to be a complex task.…”
Section: Introductionmentioning
confidence: 99%
“…At low maturity, compaction plays a dominant role. At this stage, organic pores are not developed, and mesopores (2‐50 nm) and macropores (>50 nm) in shale are decreasing . When the maturity is near the oil window, the original pores are blocked because of the large amount of liquid hydrocarbons generated.…”
Section: Factors Affecting the Adsorption Of Tcgmentioning
confidence: 99%
“…At this stage, organic pores are not developed, and mesopores (2-50 nm) and macropores (>50 nm) in shale are decreasing. 93 When the maturity is near the oil window, the original pores are blocked because of the large amount of liquid hydrocarbons generated. At this stage, micropores (<2 nm), mesopores, and macropores are continuously decreasing.…”
Section: Maturitymentioning
confidence: 99%
“…Both types of iron ore-related pores have relatively good connectivity which may provide narrow channels and permeability pathways for gas flow. 15,32,37 …”
Section: Fractal Characteristics Of Pores In Taiyuan Formation Shale mentioning
confidence: 99%